Evolution of the European network and implications for self-connection. (October 2017) - Cattaneo, Mattia; Malighetti, Paolo; Paleari, Stefano; Redondi, Renato
Abstract: Self-connection has become an appealing alternative for passengers in the European air transportation market, along with the remarkable growth of the low-cost carriers (LCCs) network over the last decade. As the development of self-connectivity is not directly designed in airports and airlines' growth strategies, this study aims to deeply understand the evolution of self-connectivity options in the intra-European market over time. By implementing a quickest travel time approach, we analyse the number of quickest connections and the share of indirect quickest paths that remained un-managed in years 2006 and 2016. Results document that, overall, travelling in Europe has become faster (−5.7 min of weighted average), while European airports' coverage, that is, airport pairs that can be directly or indirectly connected, decreased from 65% to 53%. The strong increase in LCCs' seat capacity (74%) did not translate into a similar growth of indirect connections options. Due to LCCs' offer redistribution and traditional carriers' partial retreatment from the European market to concentrate on intercontinental destinations, 1-transfer managed or un-managed options available to passengers in Europe dropped by 9.5%, and the share of 1-transfer quickest paths achievable by self-connecting flights increased by only 3pp, from 66% in 2006 to 69% in 2016. Highlights: We study the quickest connections remained un-managed over time (2006–2016) by implementing a quickest travel time approach. Travelling in Europe has become faster in the last decade (−5.7 min). European airports' coverage (direct and indirect connections) decreased from 65% to 53%. Indirect managed or un-managed options available to passengers in Europe dropped by 9.5%. The share of 2-step quickest paths achievable by self-connecting flights increased by only 3%.